Developmental stages of a common emigrant butterfly Catopsilia crocale fabricius and its association with the host plant Cassia alata (Journal of Bangladesh Academy of Sciences, 2015)
Developmental stages of pierid butterfly Catopsilia crocale Fabricius (Lepidoptera: Pieridae) and its association with Cassia alata: Family-Leguminosae (host plant) was studied in the laboratory under 24 ± 5°C temperature with RH 66 ± 2%. The host plant association and duration of developmental stages was given importance. Duration of life cycle (egg to adult) was 22.0 ± 0.8 days. The incubation period, larval and pupal period were 6.65 ± 0.4, 10.1 ± 0.8 and 6.5 ± 0.44 days, respectively. Eggs, five larval instars and pupal stages were distinct. Correlation was found among the development of larval instars, amount of food consumption and excretion of faeces. The association of C. crocale with host plant was characterized and evidenced by the use of C. alata leaves, buds, stems and shoots for egg laying and for complete development of the larval (9 - 11 days) and pupal (6 - 7 days) stages. The incubation period, different larval instars and pupal stage were found to be deeply associated with the phenological phases of the host plant.Journal of Bangladesh Academy of Sciences, Vol. 39, No. 1, 91-101, 2015